Aqueous Extract of Guava (Psidium guajava L.) Leaf Ameliorates Hyperglycemia by Promoting Hepatic Glycogen Synthesis and Modulating Gut Microbiota - Chu, Shuzhou; Zhang, Feng; Wang, Huiying; Xie, Lijun; Chen, Zhinan; Zeng, Weimin; Zhou, Zhiguang; Hu, Fang (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a major global health concern. Psidium guajava L. (guava) is widely used for food as well as a folk medicine. Previous studies have shown its anti-diabetic and anti-inflammatory properties. However, the underlying mechanisms remains to be elusive. In this study, we assessed the potential therapeutic effects of aqueous extract of guava leaves (GvAEx) on T2DM and explored their potential mechanisms in vivo and in vitro. GvAEx was gavage administered for 12 weeks in diabetic db/db mice. Our results have demonstrated that GvAEx significantly lowered fasting plasma glucose levels (p < 0.01) and improved glucose tolerance and insulin sensitivity (p < 0.01, p < 0.05, respectively). Additionally, GvAEx increased hepatic glycogen accumulation, glucose uptake and decreased the mRNA expression levels of gluconeogenic genes. Furthermore, GvAEx-treatment caused higher glucose transporter 2 (GLUT2) expression in the membrane in hepatocytes. Notably, for the first time, we have elaborated the possible mechanism of the hypoglycemic effect of GvAEx from the perspective of intestinal microbiota. GvAEx has significantly changed the composition of microbiota and increased short chain fatty acid (SCFA) -producing Lachnospiraceae family and Akkermansia genus in the gut. Taken together, GvAEx could alleviate hyperglycemia and insulin resistance of T2DM by regulating glucose metabolism in the liver and restoring the gut microbiota. Thus, GvAEx has the potential for drug development against T2DM.